2017
DOI: 10.1038/ncomms16095
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced plasmonic colours on metals

Abstract: Plasmonic resonances in metallic nanoparticles have been used since antiquity to colour glasses. The use of metal nanostructures for surface colourization has attracted considerable interest following recent developments in plasmonics. However, current top-down colourization methods are not ideally suited to large-scale industrial applications. Here we use a bottom-up approach where picosecond laser pulses can produce a full palette of non-iridescent colours on silver, gold, copper and aluminium. We demonstrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
170
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(173 citation statements)
references
References 52 publications
3
170
0
Order By: Relevance
“…Wu et al demonstrated that a Ag reflection grating with a subwavelength period of 180 nm exhibited a strong dependence on the depth of the resonant grating ( Figure ) and strong absorption for the cyan and magenta channels, although this structure is dependent on the polarization of the incident light. Thermal effects produced by direct ps laser pulses on gold and silver surfaces created nanoparticles that produced a broad gamut of angle‐robust colors …”
Section: Applicationsmentioning
confidence: 99%
“…Wu et al demonstrated that a Ag reflection grating with a subwavelength period of 180 nm exhibited a strong dependence on the depth of the resonant grating ( Figure ) and strong absorption for the cyan and magenta channels, although this structure is dependent on the polarization of the incident light. Thermal effects produced by direct ps laser pulses on gold and silver surfaces created nanoparticles that produced a broad gamut of angle‐robust colors …”
Section: Applicationsmentioning
confidence: 99%
“…Laser induced structures, such as periodical formations like grooves and spikes, are reported to induce remarkable modications of surface wetting, 7-10 tribological, 11 and optical properties. [12][13][14] Recent studies showed that LIPSS can also have an inuence on biolm adhesion on steel surfaces 15 and the growth of body cells. 16 Nowadays, such laser induced structures can be applied to create specic desired surface properties of industrial or domestic devices as well as for medical applications such as implants and surgery equipment and are therefore of very high interest.…”
Section: Introductionmentioning
confidence: 99%
“…If monodisperse or weakly polydisperse noble metal nanoparticles are gathered into a large‐scale disordered assembly with a low or moderate packing density, the spectral response of the ensemble will be very similar to that of the nanoparticles taken individually. This makes noble metal nanoparticles ideal candidates for structural coloring, which is now achieved by scalable routes such as laser writing . Physical deposition techniques, such as sputtering, are also appealing candidates for the fabrication of coatings with structural colors, as they enable controlling the size and aspect ratio of noble metal nanoparticles grown on planar substrates (2D assemblies) or embedded in thin films (2D or 3D assemblies) .…”
Section: Plasmon Resonancesmentioning
confidence: 99%